2014
DOI: 10.5812/asjsm.23073
|View full text |Cite
|
Sign up to set email alerts
|

Second to Fourth Digit Ratio Is a Predictor of Sporting Ability in Elite Indian Male Kabaddi Players

Abstract: Background:To determine the 2D:4D ratio in elite Indian male kabaddi players and compare them with non-athletes.Objectives:Our study was undertaken to find out a possible relation between digit ratio and sporting ability of male kabaddi players. This study also gives an insight into the possible ethnic differences between Indian sports personnel and other populations.Patients and Methods:Both right and left hands of 33 male kabaddi players attending training camp at the Bangalore regional centre of Sports Auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…2D:4D has consistently been shown to be a negative correlate of sports performance, athletic performance and physical fitness; individuals with low 2D:4Ds are more likely to perform better than individuals with high 2D:4Ds (Dyer, Short, Short, Manning & Tomkinson, ; Frick, Hull, Manning & Tomkinson, ; Hönekopp & Schuster, ; Hull, Schranz, Manning & Tomkinson, ; Manning & Taylor, ; Tomkinson & Tomkinson, ). This relationship was first demonstrated in English professional football (soccer) players by Manning and Taylor () and subsequently across a range of sports including (but not limited to) American football (gridiron) (Schorer, Rienhoff, Westphal & Baker, ), basketball (Dyer et al, ; Frick et al, ), cross‐country running (Manning, Morris & Caswell, ), fencing (Voracek, Reimer & Dressler, ), handball (Baker et al, ), kabaddi (an Indian contact sport) (Sudhakar, Majumdar, Umesh & Panda, ), rowing (Hull et al, ), rugby (Bennett, Manning, Cook & Kilduff, ), sprinting (Manning & Hill, ), slalom skiing (Manning, ), sumo wrestling (Tamiya, Lee & Ohtake, ), surfing (Kilduff, Cook & Manning, ), swimming (Perciavalle, Corrado, Scuto, Perciavalle, & Coco, ), tennis (Hsu et al, ), and volleyball (Panda, Majumdar, Umesh & Sudhakar, ).…”
Section: Introductionmentioning
confidence: 93%
“…2D:4D has consistently been shown to be a negative correlate of sports performance, athletic performance and physical fitness; individuals with low 2D:4Ds are more likely to perform better than individuals with high 2D:4Ds (Dyer, Short, Short, Manning & Tomkinson, ; Frick, Hull, Manning & Tomkinson, ; Hönekopp & Schuster, ; Hull, Schranz, Manning & Tomkinson, ; Manning & Taylor, ; Tomkinson & Tomkinson, ). This relationship was first demonstrated in English professional football (soccer) players by Manning and Taylor () and subsequently across a range of sports including (but not limited to) American football (gridiron) (Schorer, Rienhoff, Westphal & Baker, ), basketball (Dyer et al, ; Frick et al, ), cross‐country running (Manning, Morris & Caswell, ), fencing (Voracek, Reimer & Dressler, ), handball (Baker et al, ), kabaddi (an Indian contact sport) (Sudhakar, Majumdar, Umesh & Panda, ), rowing (Hull et al, ), rugby (Bennett, Manning, Cook & Kilduff, ), sprinting (Manning & Hill, ), slalom skiing (Manning, ), sumo wrestling (Tamiya, Lee & Ohtake, ), surfing (Kilduff, Cook & Manning, ), swimming (Perciavalle, Corrado, Scuto, Perciavalle, & Coco, ), tennis (Hsu et al, ), and volleyball (Panda, Majumdar, Umesh & Sudhakar, ).…”
Section: Introductionmentioning
confidence: 93%
“…In a meta‐analysis of 25 studies, Hönekopp and Schuster () reported that the overall relationship between 2D:4D and sporting performance was negative and small ( r = −0.26, P < 0.001) indicating that athletes with a lower 2D:4D perform better athletically. Many of the studies reviewed by Hönekopp and Schuster () examined the 2D:4D‐performance link in individual sports, with subsequent studies linking 2D:4D to team sports performance showing similar relationships (Panda et al, ; Schorer et al, ; Sudhakar et al, ). Of these studies, nearly all of the attention has been on field‐based team sports performance (e.g., soccer and rugby), with little known about the links between 2D:4D and court‐based team sports performance.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Moffit & Swanik [6], football and gymnastics athletes showed these results with high levels of significance (p = 0.000 and p = 0.001, respectively). Kabbadi players (similar to rugby) also have a lower value of 2D:4D compared to the control group (population in general, non-athlete) [41]. The same situation was observed in women, where amateur athletes have lower values of 2D:4D compared to women not engaged in sports [42].…”
Section: Several Researches Show That Athletes Of Different Sports Modal-mentioning
confidence: 56%